Screening for MPL mutations in essential thrombocythemia and primary myelofibrosis: normal Mpl expression and absence of constitutive STAT3 and STAT5 activation in MPL W515L-positive platelets - Glembotsky, Ana Claudia (2010)
OBJECTIVES: To evaluate the frequency of MPL W515L, W515K and S505N mutations in essential thrombocythemia (ET) and primary myelofibrosis (PMF) and to determine whether MPLW515L leads to impaired Mpl expression, constitutive STAT3 and STAT5 activation and enhanced response to thrombopoietin (TPO). METHODS: Mutation detection was performed by allele-specific PCR and sequencing. Platelet Mpl expression was evaluated by flow cytometry, immunoblotting and real-time RT-PCR. Activation of STAT3 and STAT5 before and after stimulation with increasing concentrations of TPO was studied by immunoblotting. Plasma TPO was measured by ELISA. RESULTS: MPLW515L was detected in 1 of 100 patients with ET and 1 of 11 with PMF. Platelets from the PMF patient showed 100% mutant allele, which was <50% in platelets from the ET patient, who also showed the mutation in granulocytes, monocytes and B cells. Mpl surface and total protein expression were normal, and TPO levels were mildly increased in the MPLW515L-positive ET patient, while MPL transcripts did not differ from controls in both MPLW515L-positive patients. Constitutive STAT3 and STAT5 phosphorylation was absent and dose response to TPO-induced phosphorylation was not enhanced. CONCLUSIONS: The low frequency of MPL mutations in this cohort is in agreement with previous studies. The finding of normal Mpl levels in MPLW515L-positive platelets indicates this mutation does not lead to dysregulated Mpl expression, as frequently shown for myeloproliferative neoplasms. The lack of spontaneous STAT3 and STAT5 activation and the normal response to TPO is unexpected as MPLW515L leads to constitutive receptor activation and hypersensitivity to TPO in experimental